KONFLIK PEMAKAMAN NON MUSLIM DI LINGKUNGAN PEMAKAMAN ISLAM DI DESA NGIMBANGAN KABUPATEN MOJOKERTO PERSPEKTIF EGALITARIAN RECIPROCITY SEYLA BENHABIB - Ardhana, Cahya; Muktafi , Muktafi (ISLAMIKA, 2024)
The burial conflict of non-Muslims in an Islamic cemetery in Ngimbangan Village, MojokertoRegency, reflects the challenges of implementing principles of justice and equality in a multicultural society. Using Seyla Benhabib's theory of egalitarian reciprocity, this study highlights the importance of treating every individual fairly, regardless of their religious background. This conflict arose due to the clash of interests between majority and minority groups. This qualitative research employs a descriptive method, relying on data collected through interviews and direct observation. The findings reveal that dialogue and deliberations involving religious leaders, local communities, and village authorities serve as a means to apply the principles of justice and equality. These efforts not only support decisions that respect minority rights but also foster collective awareness of the importance of mutual respect in interfaith relations. However, resistance from some community members who feel their interests are inadequately accommodated poses a significant challenge to the implementation of egalitarian reciprocity. This study underscores the importance of inclusive approaches in resolving such conflicts, ultimately contributing to sustainable social harmony.